2022
DOI: 10.3390/molecules27134146
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the Biofunctionalization of Straining Flow Spinning Regenerated Bombyx mori Fibers

Abstract: High-performance regenerated silkworm (Bombyx mori) silk fibers can be produced efficiently through the straining flow spinning (SFS) technique. In addition to an enhanced biocompatibility that results from the removal of contaminants during the processing of the material, regenerated silk fibers may be functionalized conveniently by using a range of different strategies. In this work, the possibility of implementing various functionalization techniques is explored, including the production of fluorescent fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In addition to the characterization of the geometrical features of the fibers, previous studies have shown that the mechanical properties of the fibers are not affected by the functionalization process [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the characterization of the geometrical features of the fibers, previous studies have shown that the mechanical properties of the fibers are not affected by the functionalization process [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The production of silk fibroin (SF) used for the manufacture of fibers is described elsewhere [ 17 ]. Silkworm cocoons were kindly provided by Professors José Luis Cenis and Salvador D. Aznar-Cervantes of the Instituto Murciano de Investigación y Desarrollo Agrario y Alimentario (IMIDA; Murcia, Spain).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation